Psychological Service as an Integral Part of the Educational System - Muradyan, Armine (ՀՀ ԳԱԱ)
This article discusses the peculiarities of psychological work, which are considered an integral part of the educational system, with a special emphasis on working with early, middle, and older adolescents. The adolescent-parent-teacher relationship is also discussed in the article in the context of psychological work. The changes taking place in all the spheres of the rapidly developing world require revising of values and establishment of new ones. After the collapse of the Soviet Union, completely new realities have been established in the post-soviet countries. The economic collapse and the hard social conditions have had an adverse impact also on the whole educational process. Since 1991 the public educational system of the Republic of Armenia, being the successor of the Soviet educational system, has entered the phase of difficult transitional changes that can be characterized as a survival period of the system. Սույն հոդվածում քննարկվում են հոգեբանական աշխատանքի առանձնահատկությունները, որոնք համարվում են կրթական համակարգի անբաժանելի մասը, կարևորվում են հատկապես վաղ, միջին և ավագ տարիքի դեռահասների հետ աշխատանքները: Դեռահաս-ծնող-ուսուցիչ եռակողմ հարաբերությունները հոդվածում քննարկվում են նաև հոգեբանական աշխատանքի համատեքստում։ Արագ զարգացող աշխարհի բոլոր ոլորտներում տեղի ունեցող փոփոխությունները պահանջում են արժեքների վերանայում և նորերի հաստատում։ Խորհրդային Միության փլուզումից հետո հետխորհրդային երկրներում բոլորովին նոր իրողություններ են հաստատվել։ Տնտեսական ճգնաժամը և սոցիալական ծանր պայմաններն իրենց բացասական ազդեցությունն են թողել նաև կրթական ողջ գործընթացի վրա։ 1991 թվականից Հայաստանի Հանրապետության հանրակրթական համակարգը, լինելով խորհրդային կրթական համակարգի իրավահաջորդը, թևակոխել է անցումային բարդ փոփոխությունների փուլ, որը կարելի է բնութագրել որպես համակարգի գոյատևման շրջան։ В данной статье рассматривается специфика психологической работы, которая считается неотъемлемой частью системы образования, с особым акцентом на работу с подростками раннего, среднего и старшего возраста. Трехсторонние отношения подросток-родитель-учитель также рассматриваются в статье в контексте психологической работы Изменения во всех сферах бурно развивающегося мира требуют пересмотра ценностей и установления новых. После распада Советского Союза в постсоветских странах установились совершенно новые реалии. Экономический коллапс и тяжелые социальные условия негативно сказались на всем образовательном процессе. С 1991 года система общего образования Республики Армения, являясь правопреемницей советской системы образования, вступила в стадию сложных переходных изменений, которую можно охарактеризовать как период выживания системы.
Keywords: Social and Humanitarian Sciences